Compensating cerebral palsy cases: problems in court litigation and the no-fault alternative - Jahn Kassim, Puteri Nemie; Ushiro, Shin; Mohd Najid, Khadijah (World Association of Medical Law, 2015)
Children having cerebral palsy will incur life-long disabilities, which require high costs of medical and nursing care. This imposes a tremendous burden on the families of the affected children, whether financially or emotionally. It is understandable for the affected families to initiate court litigation in order to alleviate the financial burden and at the same time to overcome the emotional pain associated with the permanent and lifetime implications which cerebral palsy entails. However, suing for such injuries in court and identification of medical malpractice is not an easy task for the families. Further, court litigation tends to be tedious, lengthy and unpleasant. The hazards of litigation have prompted several countries to find an available alternative to court litigation, such as the implementation of a no-fault compensation system, to settle these types of claims. Thus, it is much applauded that the Japan Obstetric Compensation System for Cerebral Palsy was established in January 2009, with the aim of helping children with such disabilities to improve their quality of life and to provide monetary compensation in order to lessen the economic burden on the family. The system features two vital pillars; that is, compensation and causal analysis prevention. The system aims at improving the quality of maternity care and analyzing the causes of accidents in order to prevent similar cases from happening in the future. Overall, the system clearly depicts social solidarity in encouraging collective responsibility for the mishaps suffered by the community.